Introducing the phytolith analysis: a suitable method in palaeoecology and landscape ecology - Pető, Ákos (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The use of silicified plant microremains in palaeoenvironmental reconstructions of landcsape evolution has not been in common use yet. Not only are phytoliths bearers of significant imformation package of soil generation process and landscape evolution, but they can be utilised to reveal important questions related to archaeology and ancient human activities.This paper intends to give a general overview of the discipline and demonstrates the use of phytolith analysis through a case study. The examination of the buried soil profiles and cultural layers of the Lyukas- mound, which is situated near Hajdúnánás on the Great Plains of Hungary, resulted in novel information on the ancient vegetational patterns and environmental conditions of the Holocene. By using the analysis of these plant microfossils, questions regarding the construction and use of kurgans could also be answered.
Keywords: phytolith analysis; palaeoecology; palaeosoils; kurgans; buried soil profiles; palaeoenvironmental reconstruction